Residual stress measurements in offshore wind monopile weldments using neutron diffraction technique and contour method - Jacob, Anaïs; Oliveira, Jeferson; Mehmanparast, Ali; Hosseinzadeh, Foroogh; Kelleher, Joe; Berto, Filippo (Elsevier, 2018)
Reliable assessment of the fatigue life of offshore wind monopiles operating in harsh offshore environments relies on quantifying the level of residual stresses locked-in at circumferential weld regions. This study presents, for the first time, residual stress characterisation, using the contour method, on a large structural welded mock-up, typical of the weldment used in offshore wind monopiles. The contour method and neutron diffraction measurements were also conducted on a compact tension specimen extracted from the large mock-up. The extracted compact tension sample, typically used for fracture and fatigue crack growth tests, showed notably significant remnant residual stresses that could impact fracture and fatigue test results. In addition the measured 2D map of transverse residual stresses, acting normal to the crack plane, playing a key role in fatigue crack opening/closure, exhibited variations through the thickness of the compact tension sample. The key conclusion was that the residual stresses in small laboratory samples extracted from large scale weldments should be carefully characterised and taken into account in structural integrity tests. Besides, the measurement results on the welded mock-up showed that the level of damaging tensile residual stress in large-scale mock-ups and hence real size structural welded monopiles is considerably larger than residual stresses in extracted laboratory samples; hence will have more significant influence on structural integrity of offshore wind assets.
Keywords: Residual stress; Monopile; Fatigue crack growth; Offshore wind; Neutron diffraction; Contour method